Pengaruh Jumlah Inokulum Sel Inang Bakteri E.coli BL21 (DE3) pLysS dan Waktu Overekspresi pada Produksi Protein Rekombinan Fim-C Salmonella typhi - Muktiningsih Nurjayadi; Izzatul Ilma Chairinnisa; Geta Putri Mentari; Dudi Hardianto; Asri Sulfianti; Kurnia Agustini (Jurnal Kimia Valensi, 2018)
Recombinant protein Fim-C S.typhi is a potential protein that can be used as an alternative typhoid vaccine and produced on a large scale. However, before entering into a large-scale stage, laboratory optimum data on the factors that affect the production process of Fim-C Salmonella typhi proteins are required. This study aims to obtain information regarding the effect of host cell number E.coli BL21 (DE3) pLysS and overexpression time on production of recombinant protein Fim-C Salmonella typhi as the basis for developing candidate of typhoid vaccine. The optimization process of overexpression was done by adding 0.5 mM IPTG (Isopropyl-β-D-thiogalactopyranoside) inducer into bacterial cultures of 2%, 4%, and 6% with 4, 5, and 6 hours over expression. The measurement of the concentration of Fim-C recombinant protein extracted samples were done by a spectrophotometric method used BCA Kit Assay Thermo ScientificTM with wavelength 590nm. The characterization of those protein extracts was performed using SDS-PAGE method. The results from the study concluded that the number of 4% E.coli bacterial cells and four-hour overexpression time are the optimum condition of Fim- C Salmonella typhi characterized by the presence of high-intensity bands at ± 31 kDa.